Computer-Assisted Management of ADHD - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2011)
Researchers at the Departments of Psychiatry and Pediatrics, Children's Memorial Hospital, Chicago, conducted a randomized medication trial for ADHD involving 24 pediatric practices.